PENGARUH KEAMANAN DAN KEPERCAYAAN TERHADAP NIAT BELI PRODUK ONLINE SHOP DENGAN NORMA SUBJEKTIF SEBAGAI VARIABEL MODERASI - Rahayu Triastity, Tutik Setyawati, Y. Djoko Suseno & (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2016)
The purpose of this study are to analyze: 1) effect of security onpurchase intention online shop, 2) effect of trust on purchase intention ofproducts online shop, 3) effect of subjective norms on purchase intention ofproducts online shop, 4) effect of security on purchase intention of productsonline shop with subjective norms as moderation variables, 5 ) effect of truston purchase intention of products online shop with subjective norms asmoderation variables. This type of research is survey at consumers atSurakarta. A sample of 100 responden with with a purposive sampling andaccidental sampling technique. Data collection technique used questionnaireand librarty research. Analysis data used researh instrument test, classicalassumption test, multiple linear regression, t-test, F-test, coefficientdetermination and test the absolute difference. The results showed that thesecurity has significant effect on purchase intention of products online shop.Trust has significant effect on purchase intention of products online shop.Subjective norms has significant effect on purchase intention of productsonline shop. Subjective norm moderating the effect of security on purchaseintention of product online shop. Subjective norm does not moderate theeffect of trust on purchase intention of product online shop.Keywords: security, trust, subjective norms and purchase intention